Peran Anggaran dan Realisasi Anggaran Produksi Film Independen dalam Perspektif Akuntansi - Erstiawan, Martinus Sony; Wangi, Mega Pandan (Universitas Nusantara PGRI Kediri, 2023)
The purpose of the study is to conduct an in-depth study of the stages of the production process starting from pre-production, production and post-production at independent production houses in recording, acknowledging, disclosing and presenting in an accounting perspective based on the budget and budget realization. The research method used qualitative methods based on literature studies / literature studies and interviews, while data analysis using interpretive discourse analysis techniques is used as a source of literature and informants with studies according to fields and science. The findings in this study reveal the budget management of independent film production houses which is closely related to making short-duration films where the realization of financial activities is carried out to finance all filmmaking activities from pre-production, production and post-production. Meanwhile, recording, presenting, and disclosing financial activities have not been fully carried out by production houses in managing their finances to be submitted to stakeholders. The contribution of this research elaborates and proves that financial activities in the field of cinema need to be a concern in managing, recording, disclosing and presenting their financial activities. The results of this study prove that recording, preparation and budget management are realized by obtaining funds from various sources and realization of expenditures through cash activities to meet the needs of pre-production, production to post-production of films.